1996
DOI: 10.1021/ja9526527
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Novel Volatile Platinum Complex for Use in CVD and a Study of the Mechanism of Its Thermal Decomposition in Solution

Abstract: The synthesis, characterization, chemical vapor deposition, and mechanistic investigation of the thermal decomposition in aromatic solvents of cis-bis(η2,η1-pent-4-en-1-yl)platinum (1) are described. Complex 1 has a unique chelated structure, giving rise to enhanced volatility, and has proved useful for the chemical vapor deposition of thin platinum films under mild conditions. Films deposited on a glass slide in a hot walled glass tube at 175 °C have an elemental composition of 82% Pt and 18% C. Kinetic, deut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 43 publications
3
44
0
Order By: Relevance
“…In a similar way, Benn et al [38] have synthesized the bis(alkenyl) complexes L 2 Pt{(CH 2 ) 2 CH CH 2 } 2 (where L 2 = dmpe, dcpe, dppe). In contrast, Tagge et al have shown that reacting Pt(COD)Cl 2 with pent-4-en-1-ylmagnesium bromide gives cis-bis( 1 , 2 -pent-4-en-1-yl)platinum (23), a complex in which the alkenyl ligand is bound to the metal in a 1 , 2 -fashion [37]. The complex Pt{(CH 2 ) 3 CH CH 2 } 2 (23) is air and moisture stable, but thermally sensitive in the solid state, decomposing within 2 weeks at room temperature.…”
Section: Bis(alkenyl) Compoundsmentioning
confidence: 96%
See 2 more Smart Citations
“…In a similar way, Benn et al [38] have synthesized the bis(alkenyl) complexes L 2 Pt{(CH 2 ) 2 CH CH 2 } 2 (where L 2 = dmpe, dcpe, dppe). In contrast, Tagge et al have shown that reacting Pt(COD)Cl 2 with pent-4-en-1-ylmagnesium bromide gives cis-bis( 1 , 2 -pent-4-en-1-yl)platinum (23), a complex in which the alkenyl ligand is bound to the metal in a 1 , 2 -fashion [37]. The complex Pt{(CH 2 ) 3 CH CH 2 } 2 (23) is air and moisture stable, but thermally sensitive in the solid state, decomposing within 2 weeks at room temperature.…”
Section: Bis(alkenyl) Compoundsmentioning
confidence: 96%
“…While there are a number of reports on monoalkenyl complexes prepared using the various synthetic methods described above, the known bis(alkenyl) complexes are limited to platinum [37,38], molybdenum [28,29] and zirconium [36], and have been prepared exclusively by reaction of a metal halide with a Grignard reagent. No other methods are known for the synthesis of alkenyl complexes of these metals (Scheme 7).…”
Section: Bis(alkenyl) Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…[21] However, many of these Pt complexes are not commercially available, and the development of a Pt-MOCVD process for commercial-scale production is primarily restricted by the low volatility and thermal stability of solid precursors. In addition, when Pt was deposited on BST using a fluorine-containing precursor, a significant amount of fluorine contamination was observed at the interface of Pt and BST.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to many other preparation methods, MOCVD is a reproducible and controllable method of producing metal ultra‐thin films or nanoparticles, tubes, or wires. This method is widely used due to its simple experimental set‐up, convenient operation, relatively low temperature conditions, and uniform deposition quality.…”
Section: Introductionmentioning
confidence: 99%